Attentional bias to cannabis cues in cannabis users but not cocaine users. (January 2019) - Alcorn, Joseph L.; Marks, Katherine R.; Stoops, William W.; Rush, Craig R.; Lile, Joshua A.
Abstract: Attentional bias to drug cues has been associated with the problematic use of drugs, including cannabis. The cognitive mechanisms underlying this bias are not fully understood. The purpose of this study was to determine whether cannabis-cue attentional bias is associated with disruptions in attentional processing. To this end, a novel cannabis-cue visual probe task that incorporated eye tracking technology and attention-based metrics derived from signal detection theory was administered to seventeen individuals who reported daily/near-daily cannabis use. Seventeen individuals with cocaine use disorder were also enrolled as a clinical-control group. Cannabis and neutral images were briefly presented side-by-side on a computer screen, followed by the appearance of a "go" or "no-go" target upon offset of both images to permit assessment of attention-based performance. Cannabis users exhibited attentional bias to cannabis cues, as measured by fixation time and response time, but not cue-dependent disruptions on subsequent attentional performance. Cocaine users did not display an attentional bias to cannabis cues but did display poorer attentional performance relative to cannabis users. These results indicate that attentional bias to cannabis cues is selective to cannabis use history and not associated with impaired attentional processing. Highlights: Signal detection metrics were successfully integrated in a modified visual-probe task using eye-tracking. Cannabis-cue attentional bias was selective for cannabis use history. Bias was not associated with cue-dependent disruptions in attentional performance.